(untitled) (Research, Society and Development, 2020)
The scarcity of water in large urban centers, where increasing demand tends to supplant supply, has been a cause for alarm. An alternative for saving the input is its reuse, which has been stimulated mainly due to the water resources law. The objective of this work is to evaluate the performance of filters in the treatment of gray waters. A study was carried out at the Federal University of Paraíba with the treatment of gray water, which was analyzed using gravel and sand filters of different sizes. Analyzes of physical, chemical and microbiological parameters were performed for samples of fresh gray water and the effluents of the three filters. An efficiency in the removal of approximately 30 to 98% of turbidity and 30 to 95% of color can be observed. The results obtained in the analyzes were compared with those established in the Resolution National Council of the Environment (CONAMA) 357/2005 complemented and altered by the resolution 430/2011, for patterns of discharge of effluents in receiving bodies. It was found that the values ​​of pH, temperature, sedimentable materials and nutrients showed acceptable levels for disposal. Coliform elimination can be achieved through disinfection. It is concluded that the filter system can be applied both for the treatment of gray waters for disposal in receiving bodies and for the reuse in the irrigation of certain cultures, without harming the environment and the health of people, plants and animals.